Long-term survival after solitary ocular metastasis following radical resection of esophagogastric junction carcinoma: a rare case report - Gao, Yangjun; Zhai, Yuru; Ma, Ning; Zhang, Xiaoling; Du, Yunyi; Zhao, Jun (Frontiers in Oncology, 2025)
BackgroundIsolated ocular metastasis from esophagogastric junction (EGJ) cancer is extremely rare, and no standardized therapeutic approach has been established to date. Reporting such cases may help clarify optimal management strategies for uncommon metastatic patterns.Case presentationWe describe a 44-year-old male patient who developed isolated ocular oligometastasis 10 months after radical EGJ cancer resection. Comprehensive evaluation confirmed left eye involvement. Following multidisciplinary team (MDT) discussion, a combined treatment plan was implemented, starting with systemic therapy consisting of docetaxel, tegafur/gimeracil/oteracil (S-1), and tislelizumab. After achieving disease stabilization, the patient underwent left eye enucleation with ocular prosthesis implantation, followed by adjuvant radiotherapy and maintenance S-1 chemotherapy. At a 55-month follow-up, he remains disease-free with an excellent performance status (PS 0).ConclusionThis case highlights that integrated multimodal therapy—including systemic and local interventions—can result in long-term survival for patients with isolated ocular metastasis from EGJ cancer. MDT-based, individualized treatment planning is essential for optimizing outcomes in rare metastatic scenarios and may inform future precision oncology approaches.